GAMBARAN SANITASI DAN KUALITAS BAKTERIOLOGIS AIR PRODUKSI PADA DEPOT AIR MINUM DI WILAYAH KERJA PUSKESMAS PUNGGELAN 1 - Puput Wulandari; Bayu Suseno (Jurnal Ilmiah Medsains, 2025)
Safe drinking water is a primary need for supporting public health. Drinking Water Depots (DWDs) are an alternative source of clean water, yet require proper supervision to ensure safety. This research aims to describe the sanitation and bacteriological quality of production water in DWDs in the working area of Puskesmas Punggelan 1. The study uses a descriptive quantitative design with a cross-sectional approach. Data were collected using observation checklists, interviews, and laboratory tests for Coliform and Escherichia coli. Results showed 65% of DWDs met sanitation standards, 100% met equipment sanitation, and 75% met hygiene standards. Bacteriological analysis revealed 45% of water samples were free from Coliform, and 85% were free from E. coli. The study concludes that while sanitation is generally met, improvements in water quality are needed to align with Indonesian Ministry of Health Regulation No. 2 of 2023.